Zinc supplementation improves heme biosynthesis in rats exposed to lead - Budi Santoso; Hertanto Wahyu Subagio; Lisyani Suromo; Henna Rya Sunomo (Faculty of Medicine, Universitas Trisakti, 2015)
BACKGROUNDLead acetate (Pb) inhibits heme biosynthesis through inhibition of δ-aminolevulinic acid dehydrogenase (δ-ALAD), copro porphyrinogenoxidase, and ferro chelatase. Zinc supplementation increases lead-bindingmetallothionein proteins. The purpose of this study was to find evidence that zinc supplementation prior to lead exposure improves heme biosynthesis in ratsMETHODSThis was a randomized post-test only control-group design study involving 28 rats assigned to 4 groups (1 control and 3 treatment groups). The treatment groups were supplemented with zinc at doses of 0.2, 0.4, and0.8 mg daily by gavage for 3 weeks. From week 4 to 13, all groups wereexposed to lead 0.5 g/kg BW/day by gavage. At the end of week 13, δ-ALAD, erythrocyte protoporphyrin (EPP), and heme concentrations were determined by means of ELISA. One-way ANOVA, followed byBonferroni’s test was used to analyse the data.RESULTSMean δ-ALAD concentrations decreased from the control group down totreatment group 3 (0.24 ± 0.20; 0.15 ± 0.15; 0.12 ± 0.11; 0.05 ± 0.06 ng/mean per unit). Mean EPP concentrations decreased from the control group down to treatment group 3 (1.96 ± 0.50; 1.24 ± 0.24; 1.03 ± 0.05; 0.62 ± 0.16 ng/mL). Mean heme concentrations increased from the controlgroup up to treatment group 3 (8.07 ± 2.64; 10.11 ± 2.27; 10.04 ± 1.65;11.41 ± 2.58 μM). ANOVA followed by Bonferroni showed that EPP concentrations differed significantly between the control group and treatment group 3 (p=0.00).CONCLUSIONZinc supplementation prior to lead exposure improves heme biosynthesis in rats exposed to lead.